Pellet impaction at identical site in both orbits - Singh, DK; Sinha, VD; Bagaria, H; Dharkar, SR (Indian Journal of Neurotrauma, 2007)
Intra orbital foreign bodies are relatively uncommon and constitute 2.9% of ocular injuries. Pellet injury of orbit is also uncommon and constitutes 2.4% of orbital injuries We present an unusual case of bilateral orbital pellet injury where both the pellets were seen at identical positions in both orbits.
Keywords: orbital trauma; pellet injuries; penetrating injuries